Odpowiedzi

Najlepsza Odpowiedź!
2009-10-19T17:37:12+02:00
(√3i1/16-2)do potęgi 2:(1i1/16-2)=(√49/16 - 2)² : (-15/16)=(-7/4 -2)² : (-15/16) = (1i3/4 -2) ² : (-15/16)= (-1/4)² : (-15/16) = 1/16 * (-16/15) = - 1/15
KONIEC


oznaczenia :
15/16 to pietnascie szesnastych
√49/16 pierwiastek z czerdziestu dziewiec szesnastych
  • Użytkownik Zadane
2009-10-19T17:41:55+02:00
=(√49/16 - 2) ² : (- 17/16) = (7/4 - 2)² : (-17/16) = (1i3/4 - 2)² : (-17/16) =
(-1/4)² : (-17/16) = 16: (-17/16) = -15.1

pozdrawiam;)